Association between socioeconomic factors and ICD implantation in a publicly financed health care system: a Danish nationwide study. Issue 7 (9th August 2017) - Winther-Jensen, Matilde; Hassager, Christian; Lassen, Jens Flensted; Køber, Lars; Torp-Pedersen, Christian; Hansen, Steen Møller; Lippert, Freddy; Christensen, Erika Frischknecht; Kragholm, Kristian; Kjaergaard, Jesper
Abstract: Aims: For patients surviving out-of-hospital cardiac arrest (OHCA) with a shockable rhythm, implantable cardioverter defibrillator (ICD) is recommended for non-reversible causes of arrest. We aimed to determine factors associated with implantation of ICD and survival in patients surviving non-AMI OHCA in a nationwide register covering all OHCAs in Denmark. Methods and results: We identified 36 950 OHCAs between 2001 and 2012, 1700 of whom were ICD naïve, ≥18 years, of non-AMI cardiac aetiology and surviving until discharge. Six hundred fifty eight patients had ICD implanted during index admission. Association to ICD implantation during index admission was analysed in logistic regression, survival was assessed using Cox regression. Implantable cardioverter defibrillator implantation increased during the study period [odds ratio (OR) 1-year increase: 1.04, 95% confidence intervals (95% CI): 1.00–1.08, P = 0.03]. Non-shockable rhythm and age ≥70 years were associated with lower odds of ICD implantation (ORnon-shockable : 0.27, 95% CI: 0.19–0.37, P < 0.001, OR70–79 years : 0.71, 95% CI: 0.52–0.98, P = 0.04, OR≥80 years : 0.13, 95% CI: 0.07–0.22, P < 0.001). Non-AMI ischaemic heart disease, highest income tertile and chronic heart failure were associated with higher odds (ORIHD : 2.51, 95% CI: 1.77–3.60, P < 0.001, ORhighest income tertile : 1.58, 95% CI: 1.06–2.23, P = 0.02, ORHF : 1.77, 95% CI: 1.35–2.32, P < 0.001). Implantable cardioverter defibrillator implantation was associated with a lower risk of mortality (HR: 0.70, 95% CI: 0.53–0.92, P = 0.01). Conclusion: Implantable cardioverter defibrillator implantation rates increased over the study period. CHF, previous IHD and high income were associated with ICD implantation, while older age and non-shockable rhythm was associated with lower odds of ICD implantation. Implantable cardioverter defibrillator implantation was associated with higher survival rates.